ONCOLOGICAL DISEASES OF THE MAXILLOFACIAL REGION (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
In this article, the epidemiological, morphological, and clinical features of oncological diseases of the maxillofacial region observed at the clinical bases of the Faculties of Dentistry and Treatment of Samarkand State Medical University during 2020-2024 were analyzed. The study was conducted in a retrospective-sectional design and examined the clinical data of 186 patients with histologically confirmed malignant tumors, the results of visual diagnostics, and the expression of immunohistochemical markers – p53, Ki-67, and EGFR. The results showed that tumors of the tongue and oral cavity predominate, squamous cell carcinoma is the most common, and high proliferative activity can increase the clinical aggressiveness of the tumor. The high proportion of patients identified in stages III-IV confirms the need to improve the early diagnosis and screening system. The study highlights the importance of molecular markers in the assessment of maxillofacial oncological pathologies.